Flame‐Retarded Epoxy Resins with a Curing Agent of DOPO‐Triazine Based Anhydride. Issue 8 (13th May 2016) - Wirasaputra, Alvianto; Yao, Xiaohao; Zhu, Yaming; Liu, Shumei; Yuan, Yanchao; Zhao, Jianqing; Fu, Yi
Abstract : An anhydride curing agent containing 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide and triazine group (2, 4, 6‐tris‐(DOPO‐methylformatephthalic anhydride‐phenoxy)‐1, 3, 5‐triazine) is synthesized and is used to enhance the flame retardancy of diglycidyl ether of bisphenol A/methylhexahydrophthalic anhydride. The curing behavior and kinetics of the system are analyzed in‐depth. The flame retardancy is improved significantly with maintained high heat resistance. Abstract : A 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO)‐triazine based anhydride (2, 4, 6‐tris‐(DOPO‐methylformatephthalic anhydride‐phenoxy)‐1, 3, 5‐triazine (TDA)) is synthesized and used as a halogen‐free flame retardant co‐curing agent for diglycidyl ether of bisphenol A/methylhexahydrophthalic anhydride (DGEBA/MHHPA) system. The conjugation of anhydride group is increased by the utilization of TDA, leading to the reduction in the curing activation energy. The cured epoxy resin passes V‐0 rating of UL 94 test with the limiting oxygen index of 32.7 vol% when the phosphorus content is only 1.5 wt%. The flame‐retarding action of triazine ring and DOPO moiety is investigated by the residue analysis and the characterization of pyrolysis gas. Due to the presence of bulky aromatic subunits in the molecular structure of TDA, the flame‐retarded epoxy resins maintain the high glass transition temperature of DGEBA/MHHPA. Besides, the moisture absorption is diminished following the usage of TDA.